Differential effects on spatial navigation of immunotoxin-induced cholinergic lesions of the medial septal area and nucleus basalis magnocellularis - Berger-Sweeney, J (J Neurosci, 1994)
The effects on anatomy and behavior of a ribosomal inactivating protein (saporin) coupled to a monoclonal antibody against the low-affinity NGF receptor (NGFr) were examined. In adult rats, NGFr is expressed predominantly in cholinergic neurons of the medial septal area (MSA), diagonal band nuclei, and nucleus basalis magnocellularis (nBM), but also in noncholinergic cerebellar Purkinje cells. Rats with immunotoxin injections to the MSA, nBM, and lateral ventricle were compared to controls on a spatial and cued reference memory task in the Morris maze. Toxin injections to the MSA slightly impaired the initial, but not asymptotic, phase of spatial navigation. Injections to the nBM impaired all phases of spatial navigation. Cued navigation, however, was not affected in either the MSA or nBM group. The ventricular injections severely affected spatial and cued navigation. Acetylcholinesterase (AChE) histochemistry and NGFr and choline acetyltransferase immunohistochemistry revealed a loss of (1) almost all NGFr-positive cholinergic neurons in the MSA and AChE fibers in hippocampus (MSA group); (2) almost all NGFr neurons in the nBM, some in the MSA, most AChE fibers in neocortex and some in the hippocampus (nBM group), and (3) almost all NGFr neurons in the MSA and nBM and their corresponding hippocampal and cortical AChE fibers (ventricular group). Cholinergic nBM projections to the amygdala were largely preserved in all groups. The amount of cholinergic fiber loss in the cortex correlated modestly, but significantly, with the severity of impairment of the asymptotic phase of performance of the spatial task. An unambiguous interpretation of the anatomical locus of behavioral deficits was not possible because of damage to cholinergic striatal interneurons (nBM group) and to noncholinergic cerebellar Purkinje cells (ventricular group). These data suggest that the cholinergic cortical system is critical to the performance of this spatial memory task. Cholinergic denervation of the hippocampus alone, however, is not sufficient to impair markedly performance of this task.